Dampak pandemi Covid-19 terhadap portofolio saham bisnis logistik transportasi laut di Indonesia - Margono, Hanif Nur Fauzi; Daulay, Iman Taufiq; Patria, Harry (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The Covid-19 pandemic has had an impact on the global economy, particularly in the logistics industry, which includes Indonesia. The goal of this study is to identify the portfolio performance of the top five Indonesian companies in the logistics sector, particularly sea transportation, and analyze the impact before and during the pandemic using a Monte Carlo simulation of the optimal risk asset portfolio two years before the Covid-19 pandemic and two years during the pandemic. Covid-19. Before (during) the Covid-19 pandemic, the optimal portfolio weight value of BULL.JK 4,99% (0,05%), PSSI.JK 92,01% (34,65%), SMDR.JK 1,40% (31,12%), TMAS.JK 1,29% (30,42%) dan WINS.JK 0,31% (3,77%). Based on the sharpe ratio, the performance of the transportation sector stock portfolio provided a high return compared to risk during the Covid-19 pandemic, from 41.71% to 297.59%, with a level of volatility that tends to be stable before and after the Covid-19 pandemic, from 41.65% to 44.56%. Based on these findings, it can be concluded that the logistics sector in sea transportation can improve performance during the Covid-19 pandemic and is worthy of investment as an investor consideration.